2011
DOI: 10.1007/s11367-011-0337-z
|View full text |Cite
|
Sign up to set email alerts
|

Carbon footprint of canola and mustard is a function of the rate of N fertilizer

Abstract: Purpose Best agricultural practices can be adopted to increase crop productivity and lower carbon footprint of grain products. The aims of this study were to provide a quantitative estimate of the carbon footprint of selected oilseed crops grown on the semiarid northern Great Plains and to determine the effects of N fertilization and environments on the carbon footprint.Materials and methods Five oilseed crops, Brassica napus canola, Brassica rapa canola, Brassica juncea canola, B. juncea mustard, and Sinapis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…In most cases, the higher nitrogen fertilizer application or irrigation rate, the greater GHG emissions per unit area during crop production (Gan et al, 2012b). Qin et al (2012) reported that nitrous oxide emissions were a linear function, and yield-scaled nitrous oxide emissions were a cubic function of the nitrogen fertilizer application rate.…”
Section: Effect Of Management Practices On Ghg Emissions and Carbon Fmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, the higher nitrogen fertilizer application or irrigation rate, the greater GHG emissions per unit area during crop production (Gan et al, 2012b). Qin et al (2012) reported that nitrous oxide emissions were a linear function, and yield-scaled nitrous oxide emissions were a cubic function of the nitrogen fertilizer application rate.…”
Section: Effect Of Management Practices On Ghg Emissions and Carbon Fmentioning
confidence: 99%
“…Best management practices (BMP) have been developed for not only producing high-quality, affordable food in sufficient quantity, but also reducing negative environmental impacts (Gan et al, 2012b). To take advantage of these opportunities and promote the development of low-carbon agriculture, a study of total GHG emissions in the form of the carbon footprint of an agro-ecosystem is of critical importance (Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, cropping intensification is recognized as a key farming strategy in reducing global warming potential (Gan et al 2012). The adoption of intercropping has significant advantages on carbon sequestration than conventional sole cropping (Asgedom and Kebreab 2011;Gan et al 2011a). For example, maize-soybean (Glycine max L.) intercropping (Dyer et al 2012) and maize-wheat intercropping (Beedy et al 2010) enhance soil carbon sequestration and reduce carbon emission significantly compared to the corresponding monocultures.…”
Section: Introductionmentioning
confidence: 99%
“…When resources are limited or when the individuals are unevenly distributed within a low-density plant stand, interplant competition for available resources can be severe as the number and size of nearby plants increase (Baumann et al 2002). Canola plant performance is a function of available resources (Gan et al 2012). Individual plants in a low-density stand likely share a greater amount of resources such as light (Sunil et al 2013), water, and nutrients (Jamont et al 2013), than those within a high-density stand.…”
Section: Resultsmentioning
confidence: 99%